Answer:
90.80
Step-by-step explanation:
6x+4
= (6)(13)+4
= 78+4
=82
3x
=(3)(13)
= 39
So we know the sides are 39 and 82
Pythagoras theorem in triangles
= a2+b2= c2
Now, we know the value of a and B but not c (the hypotenuse)
Therefore,
c2 = (39)^2 + (82)^2
= 1521+ 6724
= 8245
so, c = √8245
= 90.80 unitd
Answer:
Expression: Y = -10/3 X
Y = 10/3
Step-by-step explanation:
If Y varies directly as X, then;
Y∝X
Y = kX
k is the constant of variation
If Y = 10 and X = -3
10 = -3k
k = -10/3
Substitute k = -10/3 into the expression Y = kX
Y = -10/3 X
This gives the required expression
To get the value of Y when X = -1
Recall that Y = kX
Y = -10/3 (-1)
Y = 10/3
Hence the value of Y is 10/3
Answer:
C. The percentage of all homeowners that own at least one dog
Step-by-step explanation:
A parameter describes an entire population. Timothy is sampling from the 100 random homeowners to extrapolate their opinions onto the opinions of the entire population of homeowners.
Well you are given the equation so let's plug in for kaylib and see how many miles she can see
distance = sqrt [(3 * height) / 2]
d = sqrt [(3 *48) / 2]
d = sqrt (144 / 2)
d = sqrt (72)
d = sqrt (3 * 3 * 2 * 2 * 2)
d = 6 * sqrt (2)
You you did not list Addisons height but I will say she is at x feet above sea level. we plug in x for height:
d = sqrt [(3x) / 2]
It it says how much farther for Addison which means she can see farther. to find difference we just subtract kaylibs distance from Addison. so:
sqrt [(3x) / 2] - 6 * sqrt (2)
plug in your x and use a calculator to get a decimal approximation